IMPROVING THE STUDENTS’ READING COMPREHENSION ON NARRATIVE TEXT BY USING BUZZ GROUP TECHNIQUE AT GRADE VII OF SMP YAYASAN PERGURUAN KELUARGA PEMATANG SIANTAR ACADEMIC YEAR 2019/2020 - Ridwin Purba; Fitri Indriani Sitio (Bilingual : Jurnal Pendidikan Bahasa Inggris, 2020)
This research was aimed at improving the reading narrative text comprehension of the grade seven student of SMP YP.KeluargaPematangsiantar through the use of buzz group technique.This research is action research conducted in SMP YP.Keluarga. The subjects of the study were 26 students of VII-1 as a control class and 26 students as a experimental class of SMP YP.Keluarga in the 2019/2020 academic year. The data of this research were quantitative as the supporting data. The result in this research are teaching by using buzz groups technique can effectively improve students’ reading comprehension. From the observation, the reseacher found that during the action, the students have shown their improvement such as they were able to comprehend the text well, the situation of the teaching and learning process became more enjoyable and interesting, and all of the students were involved in the teaching and learning process. They can share their knowledge and help each other in understanding the lesson material. The students not only learn from the teacher explanation, but they can learn from their friends who also learn the same thing. From the reading narrative text comprehension test, the students’ pre-test in control class mean score was 16.47 , increasing to 6.8 in thepost-test. And the students’ pre-test in experimental class mean score was 6.2, increasing to 8.0 in the post-test. Therefore, it can be concluded that teaching reading by using buzz groups technique can improve the students’ reading narrative text comprehension